Legal Uncertainty in the Regulation of Advocates' Immunity Rights in Law Enforcement Processes in Indonesia - Runik Erwanto; Suparno Suparno (Syntax Idea)
This research aims to explore the legal uncertainty surrounding the regulation of advocates' immunity rights in the practice of law enforcement in Indonesia. Although Law Number 18 of 2003 concerning Advocates provides a legal basis for advocates' immunity, its implementation is often inconsistent and vulnerable to intervention. This potentially hampers advocates in performing their functions as independent legal enforcers free from pressure. This research also discusses efforts that can be made to create legal certainty regarding advocates' immunity rights, including the formulation of clear regulations, education for stakeholders, and strengthening the role of advocates’ associations. By increasing understanding and respect for advocates' immunity rights, it is hoped that a safer and fairer environment for advocates to carry out their profession will be created, thus supporting the rule of law in Indonesia